THE MOSQUE-BASED MEDIATION CORNER: PROMOTING EMPATHETIC AND INCLUSIVE DIALOGUE FOR SUSTAINABLE COMMUNITY HARMONY - Iffatin Nur; Budi Kolistiawan; Reni Dwi Puspitasari; Intan Putri Fadillah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT Conflict is an inevitable part of plural societies and may threaten social harmony when not managed constructively. In Indonesia, the increasing number of cases brought before courts highlights the need for alternative dispute resolution mechanisms that are accessible, participatory, and rooted in local values. This study aims to explore the concept and implementation of a Mosque-Based Mediation Corner as a community peacebuilding model through the utilization of religious institutions. The research employed a qualitative approach using the Asset-Based Community Development (ABCD) framework to identify community assets and social potentials that support peaceful conflict resolution. The research stages included community asset identification, social capital mapping, community participation strengthening, and the implementation of the Mediation Corner at Baitul Hakim Mosque, UIN Sayyid Ali Rahmatullah Tulungagung. The findings reveal that the mosque’s spiritual authority, community trust, and human resource involvement constitute key social capital in establishing an inclusive and non-litigation mediation mechanism. The integration of Islamic values, including shūrā (consultation), ‘adl (justice), and ukhuwwah (brotherhood), promotes empathetic dialogue, prevents conflict escalation, and strengthens community social cohesion. This study concludes that the Mosque-Based Mediation Corner has significant potential as a sustainable community peacebuilding model and may serve as a replicable alternative dispute resolution mechanism in multicultural societies. ABSTRAK Konflik merupakan bagian yang tidak terpisahkan dari kehidupan masyarakat plural, namun berpotensi mengganggu keharmonisan sosial apabila tidak dikelola secara konstruktif. Di Indonesia, meningkatnya jumlah perkara yang diajukan ke pengadilan menunjukkan perlunya alternatif penyelesaian sengketa yang lebih mudah diakses, partisipatif, dan berbasis nilai-nilai lokal. Penelitian ini bertujuan mengeksplorasi konsep dan implementasi Pojok Mediasi Berbasis Masjid sebagai model penciptaan perdamaian komunitas melalui pemanfaatan institusi keagamaan. Penelitian menggunakan pendekatan kualitatif dengan kerangka Asset-Based Community Development (ABCD) untuk mengidentifikasi aset dan potensi sosial yang dimiliki komunitas masjid dalam mendukung penyelesaian konflik secara damai. Tahapan penelitian meliputi identifikasi aset komunitas, pemetaan modal sosial, penguatan partisipasi masyarakat, serta implementasi Pojok Mediasi di Masjid Baitul Hakim UIN Sayyid Ali Rahmatullah Tulungagung. Hasil penelitian menunjukkan bahwa otoritas spiritual masjid, kepercayaan masyarakat, serta keterlibatan sumber daya manusia menjadi modal utama dalam membangun mekanisme mediasi yang inklusif dan non-litigasi. Integrasi nilai-nilai Islam seperti shūrā (musyawarah), ‘adl (keadilan), dan ukhuwwah (persaudaraan) dalam proses mediasi terbukti mendorong dialog empatik, mencegah eskalasi konflik, serta memperkuat kohesi sosial masyarakat. Penelitian ini menyimpulkan bahwa Pojok Mediasi Berbasis Masjid memiliki potensi sebagai model perdamaian komunitas yang berkelanjutan dan dapat direplikasi sebagai alternatif penyelesaian sengketa dalam masyarakat multikultural.